Monkey Bars and Ladders: The Importance of Lateral and Vertical Job Mobility in Internal Labor Market Careers - Thomas J. Dohmen; Ben Kriechel; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2003)
The research area of the new economics of personnel has a short but important and insightful history. Theory ahead of measurement asks for testing newly developed human resource concepts. These tests often need detailed firm-specific data. Repetition and comparison of results is key in finding out what holds true in general and what marks idiosyncrasy. In this paper, we compare results from the existing literature with the outcomes from analyzing personnel data of the Dutch aircraft manufacturer Fokker during the period January 1, 1987, the day the company started with their electronic personnel filing system, until March 15, 1996, the day the company filed for bankruptcy. We shed light on differences in the functioning of internal labor markets during periods of workforce growth and decline. We find multiple ports of entry that are concentrated in low blue and white-collar levels. New entrants are younger and have higher educational levels than incumbent workers who are promoted to similar jobs. Despite substantial variation in individual wages, careers are important as wages are strongly related to job levels. Promotion rates fall and demotion rates rise when the firm enters the stage of demise. Job-rotation improves promotion chances, stimulates wage growth, and reduces the lay-off risk.
Keywords: J41; J31; J63; 330; internal labor markets; human resource management; personnel economics; Interner Arbeitsmarkt; Erwerbsverlauf; Arbeitsmobilität; Personalwirtschaft; Lohn; Betriebszugehörigkeit; Schätzung; Luftverkehrsgesellschaft; Niederlande; Koninklijke Nederlandse Vliegtuigenfabriek; Fokker <Amsterdam>